(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Artisanal mining in Kenya where women and youth play a vital role accounts for over 60% of the gemstone mining revenue in the country. Inspite of this most miners work and live in an environment characterized by water and food scarcity. This study seeks to improve the quality of life for the artisanal miners and by extension the remote areas in Africa by providing food and water security as well as better housing solutions. Poor living conditions and nutrition contribute to poor mental and physical health.